Die rol van die patriargale diskoers in pastorale gesprekke - Muller, JC; Neethling, WG (Nederduitse Gereformeerde Teologiese Tydskrif, 2003)
The stereotypical patriarchal discourse has been part of humankind for thousands of years. Since the Second World War, rapid changes have occurred in the roles fulfilled by women. The traditional family with male headship, where the husband is employed and the wife is supposed to be at home, looking after the children, hardly exists any more. These changes have created new problems, which put pressure on both sexes. A power struggle between the sexes; uncertainty in terms of fulfilling a specific gender role; violence against women; men overreacting to the point of being weak; absent fathers, and increasing stress in a post-modern society. The pastor utilising the narrative approach can assist people to look differently at their own stories and guide them to view their own stories from a new perspective. Specific conversational questions, genograms, eco maps and reframing are ways in facilitating story-telling, story-listening and story-development. This article uses the metaphor of a minefield. The “mines” are the different problems in the patriarchal discourse; the pastor is the hearing aid being utilised by the sapper to listen to old noises in a new way. The study unfolds with a creative tension between defusing and explosion concerning a narrative approach towards the patriarchal discourse in pastoral family therapy.